Supporting Innovation in SMEs in Lebanon through a Public/Private Equity Fund : The iSME Fund - Akeel, Randa (World Bank, Washington, DC, 2013)
Lebanon is a typical example of a country where the banking sector is stable with high levels of liquidity, and where the government has put in place various incentive mechanisms and programs to encourage lending for small and medium enterprises (SMEs). These include subsidized interest payments, exemptions on compulsory reserves on creditors, and a credit guarantee program-yet lending still largely remains confined to large firms. Lebanese start-ups suffer from three substantial gaps in their country's financial environment: 1) funding at the early concept stage where entrepreneurs need to develop their ideas into a viable concept and product; 2) early stage seed funding needed when starting a company; and 3) absence of venture finance needed for the firm to reach its growth stage and beyond. The project's main component comprises an innovation in SMEs funding program (the iSME fund). The iSME fund will provide two sources of financing: US$2.5 million for Concept Development Grants (CDGs); and US$25 million for equity investment in seed, early/venture, and growth stage firms. The remaining project amount will support project management, strategic training activities, marketing, and outreach to the business community, venture capital partners, the diaspora and community at large to promote the project and the fund's beneficiary entrepreneurs.